(untitled) (Development Service Industry Management, 2024)
The aim of this article is to develop a set of content scenarios for reconstruction and development of the automotive industry in the post-war period and to describe each of these scenarios. The article proposes using scenarios as a tool for post-war reconstruction and development of the automotive industry in Ukraine. Four types of reconstruction and development scenarios for the automotive sector are considered: dynamic, content-based, structural, and market-oriented. Criteria for distinguishing each of these scenario groups are presented, along with the differences between these types. A set of content scenarios for reconstruction and development of the automotive industry in Ukraine is proposed, including: “Full Cycle Production”, “Niche Specialization for Government Orders”, “Large Assembly”, “Integration into Supply Chains for International Partners”, “Dealer Specialization in the National Market”, “Strategic Alliances”, “Re-specialization”, “Auxiliary Specialization”, “Infrastructure Development”, and “Electrification” Each scenario is described in terms of its content, along with the general and specific conditions necessary for its implementation. The article also presents suggestions for further research aimed at developing scenarios for reconstruction and development of the automotive industry in Ukraine.